Targeting TSLP With shRNA Alleviates Airway Inflammation and Decreases Epithelial CCL17 in a Murine Model of Asthma - Yi-Lien Chen; Bor-Luen Chiang (Elsevier, 2016)
Airway epithelium defends the invasion from microorganisms and regulates immune responses in allergic asthma. Thymic stromal lymphopoietin (TSLP) from inflamed epithelium promotes maturation of dendritic cells (DCs) to prime Th2 responses via CCL17, which induces chemotaxis of CD4+ T cells to mediate inflammation. However, few studies have investigated the regulation of epithelial CCL17. In this study, we used shRNA against TSLP to clarify the role of TSLP in the airway inflammation and whether TSLP affects the airway inflammation via epithelial CCL17. Specific shTSLP was delivered by lentivirus and selected by the knockdown efficiency. Allergic mice were intratracheally pretreated with the lentivirus and followed by intranasal ovalbumin (OVA) challenges. The sera antibody levels, airway inflammation, airway hyper-responsiveness (AHR), cytokine levels in bronchoalveolar lavage fluids, and CCL17 expressions in lungs were determined. In vivo, TSLP attenuation reduced the AHR, decreased the airway inflammation, inhibited the maturations of DCs, and suppressed the migration of T cells. Furthermore, the expression of CCL17 was particularly decreased in bronchial epithelium. In vitro, CCL17 induction was regulated by TSLP. In conclusion, TSLP might coordinate airway inflammation partially via CCL17-mediated responses and this study provides the vital utility of TSLP to develop the therapeutic approach in allergic airway inflammation.